Coastal urbanization may indirectly positively impact growth of mangrove forests - Shan Wei; Hongsheng Zhang; Zhenci Xu; Guanghui Lin; Yinyi Lin; Xindan Liang; Jing Ling; Alison Kim Shan Wee; Hui Lin; Yuyu Zhou; Peng Gong (Communications Earth & Environment)
Abstract Coastal urbanization is a key driver of mangrove loss, yet its global impacts on mangroves have yet to be thoroughly understood. Here we present a fine-scale assessment of the hidden impacts of urbanization on mangroves mediated by climate, and the joint effects of urbanization and climate at the global scale. Surprisingly, both urbanization and climate had positive impacts on mangrove growth and carbon stock in some regions, which is different from the general belief of the adverse impacts from previous research. In total, 27.3% of global mangroves received positive impacts from urbanization regarding their extent and carbon stock, among which 59.5% are indirectly mediated by climate. Moreover, mangroves in subtropical/temperate climate zones experienced more indirect positive impacts from urbanization, which enhances local climate conditions for growth by altering temperature, rainfall and sea levels. These findings suggest the feasibility of facilitating mangrove conservation through effective urban planning to achieve coastal sustainability.